THE RELATIONSHIP OF PARENTING PARENTS WITH DIFFICULT EATING BEHAVIOR IN PRESCHOOL CHILDREN IN LAMONGAN - Ulandari, Nanis; Fitriyah, Erna Tsalatsatul; Rozi, Fahrur (WELL BEING, 2019)
Parents have an obligation and are responsible for caring for, caring for, educating, and protecting children. Difficult eating behavior in children can be characterized by refusing food to consume food or drink with the type and amount according to age. This study aims to analyze the relationship between parenting parents with difficult eating behaviors in preschool children. This research uses correlation analytic design with cross sectional approach. The sample used was 42 respondents. The sampling technique used is total sampling. Data collection using a questionnaire. The results showed that most respondents adopted democratic parenting 26 respondents (61.9%), while the majority of respondents with the criteria for difficult eating behavior were 24 respondents (57.1%). Data analysis using Chi-Square statistical test results obtained p value = 0.007 <α = 0.05, then there is a relationship between parenting parents with difficult eating behavior in pre-school children. The level of relationship is in the medium category where the correlation value is 0.483. Democratic parenting upholds openness in recognition of children's opinions and cooperation, children are given freedom but freedom can be accounted for. Keywords: Parenting Parenting, Difficult Eating Behavior, Preschoolers